Analisis Gaya, Motivasi Dan Respon Siswa Dalam Pembelajaran Geografi di MA Darul Ihsan Samarinda - Vera Mauliani Achmad; Iya' Setiyasih; Aisyah Trees Sandy (Student Scientific Creativity Journal, 2024)
Learning is the core of an education has an important role in advancing the welfare and human resources, one of which is in terms of teaching and learning. The purpose of this study is to determine learning styles, student motivation and student responses in learning geography. Geography learning styles that will be the focus of researchers in this study are visual, auditorial, and kinesthetic learning styles Motivation is one of the steps or factors that can encourage students to behave using feelings and reactions in geography learning activities. The results of research on class X students consisting of 34 female students, class XI consisting of 26 female students and class XII consisting of 35 male students at MA Darul Ihsan Samarinda. Based on the results of the study, the majority of learning styles owned by class X students are visual as many as 34 students, then class XI students are mostly kinesthetic as many as 26 students, as well as class XII the majority of kinesthetic learning styles as many as 35 students Each class has a different learning style and has each learning style. Every student basically has motivation in themselves, be it external or internal motivation. The sample in this study was class X consisting of 34 female students, XI IPS1 consisting of 26 female students, XII IPS2 consisting of 35 male students at MA Darul Ihsan Samarinda. The sample technique used is Random Sampling. Based on the results of data recap that has been done on the student learning motivation questionnaire has motivation in the good category, from these results it can be said that 34 students have good motivation, then in the category as many as 26 students have a category Less, then as many as 35 students have a good category. Based on data analysis that has been carried out on student learning responses in classes X and XI, it is found that student learning responses are in the good category with a total of 60 students or equivalent to 64%. Then in the very good category with 35 students or equivalent to 65%. The high learning response can be seen from the various indicators that have been analyzed.